Perencanaan dan Perancangan Hunian Lansia yang Ergonomis di kota Denpasar - Wibawa, I Dewa Putu Satria; Parwata, I Wayan; Linggasani, Made Anggita Wahyudi (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2022)
Elderly is where individuals over the age of 60 who generally experience a decline in some biological, psychological, and social functions. When an individual has reached old age, and their children have formed their own family, the elderly's responsibility to their children, and they return free as in the early days of their marriage. But by the time that freedom was gained, he had been in a phase with biological and psychological physical conditions that had regressed, as well as the loss of their children from home because they had formed a new family. The existence of the elderly is still often assumed negatively, where the elderly are considered a burden on the family. This arises because it looks from kasuistic towards the elderly whose lives have a dependency on others. The older a person ages, the more they need a place to shelter and get attention, especially from family. But in reality in the field many elderly who ended up abandoned by his family until entrusted in the elderly residence. In Indonesia itself, elderly housing has negative connotations because it is still associated with nursing homes where in fact there are many cases of nursing home facilities that are not habitable for the elderly and also their level of care. So that facilities that should be able to help the lives of the elderly even become a scary scourge.